INTEGRATING NEUROPHYSIOLOGICAL AND PARACLINICAL FINDINGS FOR DIFFERENTIAL DIAGNOSIS OF SUBACUTE SCLEROSING PANENCEPHALITIS IN PEDIATRIC PATIENTS - Saidazizova, Шахло; Inomov, Фирдавс (International Journal of Scientific Pediatrics, 2025)
Relevance. Subacute sclerosing panencephalitis (SSPE) remains a devastating progressive encephalopathy in children, caused by persistent measles virus infection. Accurate differential diagnosis requires integrating clinical, neurophysiological, and paraclinical data. Materials and methods.This study analyzed 180 pediatric SSPE patients treated at the Center for the Development of Professional Qualification of Medical Workers and the National Children’s Medical Center between 2019 and 2024. Data included demographics, vaccination status, disease severity, electroencephalography (EEG), and magnetic resonance imaging (MRI). Results: Characteristic EEG periodic complexes and MRI white-matter abnormalities strongly correlated with clinical stage and functional decline. Vaccination coverage was low (40%), highlighting persistent susceptibility to measles-related complications. Our findings confirm that combining EEG, MRI, and cerebrospinal fluid antibody testing increases diagnostic certainty and distinguishes SSPE from mimicking neurological conditions. Conclusion. Early recognition through multimodal assessment is essential for timely management, counseling, and trial enrollment. Strengthening vaccination strategies and standardized diagnostic protocols may reduce disease burden and improve outcomes.